Transciption regulation in bacteria and its growth-dependence - Ruifen, Li (2016)
Genetic transcription is the first step for gene expression. Without transcription, it is impossible for organism to transfer the genetic information to translation and eventually realize its normal function via proteins. The regulation of transcription is very important to ensure the accurate heredity of genetic information. Growth rate is a crucial characteristic for exponentially growing bacteria and thus lots of macromolecules including gene expression production is usually growth-dependent. Lots of studies have been focused on global growthdependence of gene expression while not so much researches and reviews focused on transcription’s growth-dependence. Promoters, sigma factors and RNA polymerase are important regulatory factors in transcription initiation, elongation and termination. However normal transcription involves not only regulatory factors but also need sufficient free and available raw materials like RNA polymerase, and growth rate will also impact the promoter activity and strength. Moreover, what is the relationship between sigma factors and bacterial global growth? This report reviews recent studies and investigates the detailed functions of promoters, sigma factors and RNA polymerase and their growth-dependence in bacteria. More importantly, we discuss how growth rate can affect promoter activity and strength, relationship between RNA polymerase and growth rate, how sigma factors involve in bacterial growth. It concludes that some transcription elements are growth-rate dependent like RNAP, alternative sigma factors like σ38, the strength of constitutive promoters; some are irrelevant with growth-rate, like total RNAP, core RNAP and housekeeping sigma factors such as σ70.